Multicenter, randomized, double‐blind phase 2 trial of FOLFIRI with regorafenib or placebo as second‐line therapy for metastatic colorectal cancer. Issue 15 (15th June 2018) - Sanoff, Hanna K.; Goldberg, Richard M.; Ivanova, Anastasia; O'Reilly, Seamus; Kasbari, Samer S.; Kim, Richard D.; McDermott, Ray; Moore, Dominic T.; Zamboni, William; Grogan, William; Cohn, Allen Lee; Bekaii‐Saab, Tanios S.; et al.
Abstract : BACKGROUND: Regorafenib, a multikinase inhibitor that inhibits angiogenesis, growth, and proliferation, prolongs survival as monotherapy in patients with refractory colorectal cancer. This international, double‐blind, placebo‐controlled, multicenter trial assessed the efficacy of regorafenib with folinic acid, fluorouracil, and irinotecan (FOLFIRI) as a second‐line treatment for metastatic colorectal cancer. METHODS: Patients with metastatic colorectal cancer who progressed on first‐line oxaliplatin and fluoropyrimidine enrolled at 45 sites in the United States and Ireland. Patients, stratified by prior bevacizumab use, were randomized 2:1 to regorafenib or placebo. The treatment consisted of FOLFIRI on days 1 and 2 and days 15 and 16 with 160 mg of regorafenib or placebo on days 4 to 10 and days 18 to 24 of every 28‐day cycle. Crossover was not allowed. The primary endpoint was progression‐free survival (PFS). Under the assumption of a 75% event rate, 180 patients were required for 135 events to achieve 90% power to detect a hazard ratio (HR) of 0.65 with a 1‐sided α value of .1. RESULTS: One hundred eighty‐one patients were randomized (120 to regorafenib‐FOLFIRI and 61 to placebo‐FOLFIRI) with a median age of 62 years. Among these, 117 (65%) received prior bevacizumab or aflibercept. PFS was longer with regorafenib‐FOLFIRI than placebo‐FOLFIRI (median, 6.1 vs 5.3 months; HR, 0.73; 95% confidence interval [CI], 0.53‐1.01; log‐rank P = .056). The median overall survival was not longer (HR, 1.01; 95% CI, 0.71‐1.44). The response rate was higher with regorafenib‐FOLFIRI (34%; 95% CI, 25%‐44%) than placebo‐FOLFIRI (21%; 95% CI, 11%‐33%; P = .07). Grade 3/4 adverse events with a >5% absolute increase from regorafenib included diarrhea, neutropenia, febrile neutropenia, hypophosphatemia, and hypertension. CONCLUSIONS: The addition of regorafenib to FOLFIRI as second‐line therapy for metastatic colorectal cancer only modestly prolonged PFS over FOLFIRI alone. Cancer 2018. © 2018 American Cancer Society . Abstract : In a double‐blind, phase 2 randomized controlled trial, the addition of regorafenib to folinic acid, fluorouracil, and irinotecan (FOLFIRI) only modestly prolongs progression‐free survival in comparison with a placebo and FOLFIRI (hazard ratio, 0.73; 95% confidence interval, 0.53‐1.01).